Energy-dispersive diffraction studies of inert anodes - Scarlett, N.; Madsen, I.; Evans, J.; Coelho, A.; McGregor, K.; Rowles, Matthew; Lanyon, M.; Urban, A. (IUCr Journals, 2009)
A tomographic study of electrochemical cells to observe scales formed on inert anodes has been conducted using energy-dispersive synchrotron X-ray diffraction. This study is preparatory to an investigation that will observe this formation in situ during the cells' operation. The purpose of the current work was to determine whether this technique would be appropriate for such a study in terms of its sensitivity and whether the results could be quantified satisfactorily. A method has been developed for the quantitative phase analysis of energy-dispersive data using crystal-structure-based Rietveld refinement. This has been tested with standard materials and found to be comparable in accuracy to results obtained from traditional angular-dispersive diffraction. The lower limits of detection of the method have not been established quantitatively but qualitative differences can be seen between cells that have been cycled at different times. These differences indicate a linear relationship between scale formation and electrolysis time.